2013
DOI: 10.1038/clpt.2013.117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approval Success Rates for Investigational Cancer Drugs

Abstract: We examined development risks for new cancer drugs. For the full study period, the estimated clinical approval success rate for cancer compounds was 13.4% (9.9% for the first half of the study period, 19.8% for the second half). Small molecules had a somewhat higher clinical approval success rate than did large molecules (14.3 vs. 11.5%). Compounds studied solely in hematologic indications had markedly higher estimated clinical approval success rates than did compounds studied only in solid tumor indications (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 14 publications
4
119
0
2
Order By: Relevance
“…One important finding emerging from the survey of cost studies in Table 1 is that clinical success rates are substantially lower for the studies focused on more recent periods. This observed trend is consistent with other analyses of success probabilities (DiMasi et al, 2010;DiMasi et al, 2013;Hay et al, 2014;Paul et al, 2010) and our analysis below. Average R&D (inflationadjusted) cost estimates are also higher for studies focused on more recent periods, suggesting a growth in real R&D costs.…”
Section: Previous Studies Of the Cost Of Pharmaceutical Innovationsupporting
confidence: 82%
“…One important finding emerging from the survey of cost studies in Table 1 is that clinical success rates are substantially lower for the studies focused on more recent periods. This observed trend is consistent with other analyses of success probabilities (DiMasi et al, 2010;DiMasi et al, 2013;Hay et al, 2014;Paul et al, 2010) and our analysis below. Average R&D (inflationadjusted) cost estimates are also higher for studies focused on more recent periods, suggesting a growth in real R&D costs.…”
Section: Previous Studies Of the Cost Of Pharmaceutical Innovationsupporting
confidence: 82%
“…By 2012, the activities of an operational efficiency working group eliminated redundancy in the review process and reduced median time to trial activation by 50% for phase III trials and 30% for early phase trials [21]. These timelines continue to improve, with a goal of achieving a median time to trial activation of 7 months for phase I and II trials and 10 months for phase III trials [4]. A significant contributor to shortened trial-activation time has been streamlined processes for the two NCI central institutional review boards (IRBs), one for adult trials and one for pediatric trials, in addition to updated consent templates [22].…”
Section: Progress Made Since the 2010 Iom Consensus Reportmentioning
confidence: 99%
“…Because therapeutic response in the treatment of metastatic disease is often the most rapid path to regulatory approval, there have been relatively few adjuvant treatment trials for solid tumors in recent years. In a study of oncology drug development from 1999 to 2012, DiMasi et al found that of the 77 cancer drugs evaluated in phase III studies of any solid tumor type, only 12 (16%) had been studied in an adjuvant setting [4].…”
Section: Challenges and Opportunities In Cancer Clinical And Translatmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite remarkable advances, elucidating the mechanisms underlying tumor establishment and progression still appears incomplete [1]. This lack of deep understanding is responsible for the partial success in the cure of cancer patients and our failure to eradicate cancers in the vast majority of patients [2][3][4]. Among many of the caveats, which have weakened major successes, a major issue remains in the lack of reliable models that can extensively reproduce human cancers and all their multifaceted features [3,5].…”
Section: Introductionmentioning
confidence: 99%